2020
DOI: 10.1016/j.jamda.2020.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Associated Factors Among Health Care Workers in Singapore During the COVID-19 Pandemic

Abstract: Objectives The strain on healthcare systems due to the COVID-19 pandemic has led to increased psychological distress among healthcare workers (HCWs). As this global crisis continues with little signs of abatement, we examine burnout and associated factors among HCWs. Design Cross-sectional survey study. Setting and Participants Doctors, nurses, allied health professionals, administrative and support staff in four public hospitals and one prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
210
3
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(265 citation statements)
references
References 52 publications
28
210
3
24
Order By: Relevance
“…Our study also demonstrated that burnout symptoms that emerged during the COVID-19 crisis depreciate extra-role performance through the work disengagement mediator, conditional on financial insecurity (a boundary condition) for increased work disengagement. The present study provides empirical evidence on the direct link between burnout and disengagement of work, which is similar to previous findings ( Tan et al, 2020 ). Our study confirmed the significance of this direct relationship in congruence with the conditional on an elevated level of financial insecurity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study also demonstrated that burnout symptoms that emerged during the COVID-19 crisis depreciate extra-role performance through the work disengagement mediator, conditional on financial insecurity (a boundary condition) for increased work disengagement. The present study provides empirical evidence on the direct link between burnout and disengagement of work, which is similar to previous findings ( Tan et al, 2020 ). Our study confirmed the significance of this direct relationship in congruence with the conditional on an elevated level of financial insecurity.…”
Section: Discussionsupporting
confidence: 92%
“…When their employers in mandatory quarantine are unable to provide job protection and income replacement, employees are likely to experience a complicated array of negative emotions and work stress that may impair their work effort and resources. Previous studies on post-coronavirus outbreaks have reported that employees who engaged in any outside employment tend to suffer from enormous financial stress, anxiety, and social isolation that affect their health and productivity ( Banerjee and Rai, 2020 ; Tan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, our study ndings regarding predictors of burnout were found to be consistent with many studies that addressed HCPs were exposed to higher levels of psychological distress due to the risk of catching COVID-19 infection and higher workload during the pandemic crisis, making them vulnerable to burnout [44][45][46][47]. Higher workload and long duty hours lead to more exposure to patients, especially among physicians and other HCPs who work directly in managing COVID-19 cases and those who work at emergency units.…”
Section: Discussionsupporting
confidence: 86%
“…To be noted, work experience was generally considered to be beneficial to mental health when treating with emergency public health incidence (25); in our study, longer ICU work time was unexpectedly identified detrimental to maintain mental health. This could be explained by the high prevalence of occupational burnout among ICU healthcare workers especially for those who had worked long years in current occupation, since occupational burnout had been proved to be associated with depressive and anxiety symptoms (26)(27)(28)(29)(30). This result raised concern about occupational burnout among ICU healthcare workers with long years of working.…”
Section: Discussionmentioning
confidence: 99%